Life and action : elementary structures of practice and practical thought - Thompson, Michael, 1959- (Harvard University Press, 2008)
Any sound practical philosophy must be clear on practical concepts--concepts, in particular, of life, action, and practice. This clarity is Michael Thompson's aim in his ambitious work. In Thompson's view, failure to comprehend the structures of thought and judgment expressed in these concepts has disfigured modern moral philosophy, rendering it incapable of addressing the larger questions that should be its focus.